Peran Kewirausahaan Digital dalam Pengembangan UMKM di Padang Lawas Utara - Hardana, Ali; Efendi Siregar, Sulaiman; Novriansyah Harahap, Takdir (CV. Raskha Media Group, 2026)
This study aims to analyze the role of digital entrepreneurship in the development of Micro, Small, and Medium Enterprises (MSMEs) in Padang Lawas Utara Regency. The advancement of information and communication technology has created new opportunities for MSMEs to enhance their competitiveness through the utilization of digital platforms. This research employs a qualitative approach, with data collected through interviews, observations, and documentation involving MSME actors. The results indicate that digital entrepreneurship plays a significant role in expanding market access, improving operational efficiency, and strengthening the branding of local products. However, several challenges remain, including limited digital literacy, uneven technological infrastructure, and a lack of training and mentoring support. Therefore, collaboration among the government, business actors, and other stakeholders is necessary to improve the digital capacity of MSMEs. By optimizing digital entrepreneurship, MSMEs in Padang Lawas Utara are expected to grow sustainably and contribute to regional economic development.